Experimental investigation of the effect of in-plane vibrations on friction for different materials. (July 2016) - Wang, Peng; Ni, Hongjian; Wang, Ruihe; Li, Zhina; Wang, Yong
Abstract: The friction between different materials in sliding plane at a frequency of 0–500 Hz has been studied. It was found that the friction is greatly affected by the external in-plane vibrations, with the maximal friction reduction occurred at higher ratio of vibrating velocity and sliding velocity being about 100%. The experimental friction coefficient tends to a higher value at lower sliding velocity ratio compared with the theoretical prediction, which can not only be attributed to the magnitude and direction change of friction in the sliding direction, but also the stick-slip motion and normal vibration. The results provide an insight into the friction research under in-plane vibrations and have guiding significance in the development of friction reduction technology by vibrating drill-string. Highlights: The friction between different materials is greatly affected by external in-plane vibrations. Stick-slip motion and normal vibration are two main reasons for deviation between theoretical and experimental results. Effect of longitudinal and transverse vibrations on friction coefficient is compared. Empirical formula of friction coefficient is derived from dimensionless analysis.